1990
DOI: 10.1055/s-2008-1071454
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Evoked Potentials in Term and Preterm Infants in Relation to Postconceptional Age and Birth Weight

Abstract: The effect of age on the maturation of median nerve somatosensory evoked potentials (SEPs) was studied in 103 normal neonates (24 preterm, 79 term) at the postconceptional age (PCA) of 36-48 weeks. The influence of birth weight was evaluated in 44 term neonates, aged 0-7 days, according to their gestational age (GA) stratified into three groups: A: 38-39 weeks (n = 15); B: 39.5-40.5 weeks (n = 15); C: 41-43 weeks (n = 14). The mean birth weight was not different in the three groups. For all infants the N13 lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…We demonstrated that preterm infants, although without major brain injury, exhibited longer N1 latencies and CCTs, lower amplitudes, and more frequently abnormal SEPs compared to their pair born at term. Our results are supported by those of Smit [ 29 ], who reported that preterm infants presented greater N1 peak latencies compared to full-term babies, both at TEA and at 6 months CA [ 11 , 13 , 30 , 31 ]. These findings could suggest that extrauterine maturation of the somatosensory pathway in very preterm newborns might be delayed compared to the maturation in full-term infants [ 11 , 13 , 30 , 31 ], possibly because of a delay in central myelination but also for the immature functioning of the synapses [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We demonstrated that preterm infants, although without major brain injury, exhibited longer N1 latencies and CCTs, lower amplitudes, and more frequently abnormal SEPs compared to their pair born at term. Our results are supported by those of Smit [ 29 ], who reported that preterm infants presented greater N1 peak latencies compared to full-term babies, both at TEA and at 6 months CA [ 11 , 13 , 30 , 31 ]. These findings could suggest that extrauterine maturation of the somatosensory pathway in very preterm newborns might be delayed compared to the maturation in full-term infants [ 11 , 13 , 30 , 31 ], possibly because of a delay in central myelination but also for the immature functioning of the synapses [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are supported by those of Smit [ 29 ], who reported that preterm infants presented greater N1 peak latencies compared to full-term babies, both at TEA and at 6 months CA [ 11 , 13 , 30 , 31 ]. These findings could suggest that extrauterine maturation of the somatosensory pathway in very preterm newborns might be delayed compared to the maturation in full-term infants [ 11 , 13 , 30 , 31 ], possibly because of a delay in central myelination but also for the immature functioning of the synapses [ 32 , 33 ]. Conversely, two other studies did not confirm our results; both studies included infants of older GA with a greater birth weight (GA < 37 weeks and birth weight > 1500 gr), compared to our cohort [ 31 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The recording epoch needs to be long, as the components appear at 200-500 ms; a sweep of 1 second is recommended. The waveforms are large, however, and only a few trials (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) are needed per average. Pryds et al 14 report reliable VEPs in premature infants recording only three trials, using very long interstimulus intervals.…”
Section: Flash Vepsmentioning
confidence: 99%
“…The selection criteria for this with four groups of term infants: with and without CHT, and group have been described previously (16). In essence, all infants with and without EHB.…”
Section: Methodsmentioning
confidence: 99%